Benzo[a]pyrene enhances lipid peroxidation induced DNA damage in aorta of apolipoprotein E knockout mice - Godschalk, Roger; Bartsch, Helmut; Nair, Jagadeesan (Free radical research, 2009)
The genotoxic compound benzo[a]pyrene (B[a]P) enhances atherosclerotic plaque progression, possibly by inducing oxidative stress and subsequent lipid peroxidation (LPO). Since LPO plays a key role in atherosclerosis, stable LPO derived DNA modifications such as 1,N6-ethenodeoxyadenosine (εdA) and 3,N4-ethenodeoxy-cytidine (εdC) may be useful biomarkers for in vivo oxidative stress. In this study, benzo[a]pyrene-diol-epoxide (BPDE)-DNA, εdA and εdC were determined by 32P-postlabelling in apolipoprotein E knockout (ApoE-KO) mice treated with 5 mg/kg B[a]P by gavage. After 4 days, BPDE-DNA adduct levels were higher in aorta (10.8±1.4 adducts/108 nucleotides) than in lung (3.3±0.7, P<0.05), which is a known target organ for B[a]P. Levels of εdA were higher in aorta of B[a]P-exposed animals than in unexposed controls (8.1±4.4 vs 3.4±2.1 adducts per 108 parent nucleotides, P<0.05). On the other hand, εdC levels were not affected by B[a]P exposure. Serum low density lipoprotein (LDL) levels were lower in B[a]P-exposed mice than in controls (9.3±3.7 and 13.3±4.0 mmol/l, respectively), whereas high density lipoprotein (HDL) levels were higher (1.4±1.6 and 0.4±0.3 mmol/l, respectively). Consequently, a three-fold difference in the LDL/HDL ratio was observed (P=0.001). εdA levels were positively related with plasma HDL concentrations (R=0.68, P=0.02), suggesting that the HDL mediated protection of the vessel wall against reactive lipid peroxides was reduced in B[a]P-exposed apoE-KO mice. Our observations show that direct as well as lipid peroxidation induced DNA damage is formed by B[a]P in aorta of apoE-KO mice, which may be involved in atherosclerotic plaque progression. This study further indicates that etheno-DNA adducts are useful biomarkers for in vivo oxidative stress in atherosclerosis.